2016
DOI: 10.1016/j.tig.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Bacterial Communities by in situ Microbiome Engineering

Abstract: Microbial communities inhabit our entire planet and play a crucial role in biogeochemical processes, agriculture, biotechnology, and human health. Here, we argue that “in situ microbiome engineering” represents a new paradigm of community-scale genetic and microbial engineering. We discuss contemporary applications of this approach to directly add, remove, or modify specific sets of functions and alter community-level properties in terrestrial, aquatic, and host-associated microbial communities. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
191
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(194 citation statements)
references
References 73 publications
1
191
0
2
Order By: Relevance
“…The first tactic involves the introduction or elimination of selected microbial taxa from the host. 68 This approach was successfully tested in animal models of inflammatory bowel disease, 911 arthritis, 12 colon cancer, 13 cystic fibrosis, 14 and depression, 15 resulting in the restoration of disease-free phenotypes. This method was also effectively used in humans to restore resilience against Clostridium difficile colonization.…”
mentioning
confidence: 99%
“…The first tactic involves the introduction or elimination of selected microbial taxa from the host. 68 This approach was successfully tested in animal models of inflammatory bowel disease, 911 arthritis, 12 colon cancer, 13 cystic fibrosis, 14 and depression, 15 resulting in the restoration of disease-free phenotypes. This method was also effectively used in humans to restore resilience against Clostridium difficile colonization.…”
mentioning
confidence: 99%
“…With the recent revolution in genome engineering capabilities to manipulate microbes and higher-order organisms [2], the scale up of microbiome engineering to systems with more complex functions in dynamic environments is poised to become an exciting and fruitful endeavor for synthetic biology. New opportunities to engineer microbial communities in open and changing environments will require next-generation in situ approaches [61]. The bottom-up study of synthetic communities will likely yield a better understanding for natural microbial ecology by systematically evaluating individual parameters in a controlled environment in an iterative design-test-learn cycle.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…It will also be necessary to fully understand the functional redundancy of the microbiome in invasive phytophagous insects to avoid functional compensation of the disrupted invasive traits. Finally, thoroughly testing the solutions in the field will be required as it has been previously shown that responses of hosts to "microbiome engineering" are not necessarily long-lasting (Sheth et al 2016), and unexpected variation in hosts/environmental conditions might occur.…”
Section: Outcomes and Important Considerationsmentioning
confidence: 99%